RELATIONSHIP OF MYOSTATIN GENE POLYMORPHISM WITH SOME GROWTH TRAITS OF COMMON CARP CYPRINUS CARPIO L. - & Saleh, Al-Khshali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was aimed to investigate the polymorphism of the myostatin gene and its relation with some growth traits,included feed conversion rate and efficiency, protein intake and protein efficiency ratio in 68 specimens of common carp Cyprinus carpio. Sequencing of single nucleotide polymorphism (SNP) showed three genotypes at site T2230C in the myostatin gene. The distribution rates were 5.88, 38.24 and 55.88% for TT, TC and CC respectively, and the variation among them was high significant, the allelic frequency was 0.25 for allele T, while it was 0.75 for C. Effect of the genotype of the myostatin gene was significantly in the feed conversion rate and efficiency, the protein intake and the protein efficiency ratio of the common carp with the variation of the genotypes of myostatin gene, whereas the feed conversion rate was 6.18 , 6.00 and 4.50 at TC , TT and CC respectively. Based on the mentioned results , the positive relation between myostatin gene polymorphism with some growth traits observed in this study may be a useful biomarker in the selection and crossing the genotypes that have achieved the best performance in common carp .